Clinical profile of wheeze in children between 6-60 months of age: a cross-sectional study in South India - R., Afraneha; Pasha, Touheer; A. P., Krithika; T., Hariharasudhan (International Journal of Research in Medical Sciences, 2025)
Background: The occurrence of wheezing is notably high among young children and represents a significant public health concern due to its impact on respiratory health and quality of life. Roughly 25–30% of infants’ experience at least one episode of wheezing during their first year of life, often triggered by viral respiratory infections or environmental exposures. By the age of three, this figure rises to approximately 40% of children, and by six years of age, nearly half of all children will have had at least one wheezing episode. These episodes can range from mild and transient to more persistent and recurrent forms, which may indicate underlying conditions such as asthma. Wheezing in early childhood is influenced by a complex interplay of genetic, clinical, and environmental factors, including family history of atopy or asthma, poor nutritional status, exposure to allergens or pollutants, and incomplete immunization. Early identification of children at risk and understanding the contributing factors is essential for timely intervention and prevention of long-term respiratory complications. Methods: A cross-sectional observational study was conducted among 123 children attending a tertiary care hospital. Information was collected regarding socio-demographic profile, family history, immunization status, and weight, along with a complete clinical history and physical examination. Results: Wheezing was most commonly observed in early childhood, affecting 28.5% of children aged 2–3 years and 26.8% of those aged 1–2 years. Among children who experienced wheezing, there was a slight female predominance, with 52.8% being girls. Additionally, 35.8% of the children were underweight, which may increase their susceptibility to wheezing. Notably, half of the children (50.4%) had a family history of wheezing or asthma, and more than half (53.7%) were not fully immunized, highlighting the role of both genetic predisposition and potentially preventable risk factors in the occurrence of wheezing. Conclusions: This study highlights that wheezing is prevalent in early childhood, particularly between 1 and 3 years of age. A significant proportion of affected children are underweight and have incomplete immunization, pointing to potential contributing factors. Furthermore, a family history of wheezing or asthma is a common finding, underscoring the role of genetic predisposition. These findings suggest the importance of addressing nutritional status, improving vaccination coverage, and considering family history in managing and preventing wheezing in young children.